2013
DOI: 10.1002/bdd.1838
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics and toxicities of methotrexate in healthy and collagen‐induced arthritic rats

Abstract: Methotrexate (MTX) is an anchor drug used to treat rheumatoid arthritis (RA), but responsiveness is variable in effectiveness and toxicity. Methotrexate and its polyglutamate conjugates (MTXPGn) in red blood cells (RBC) have been associated with patient response. In the current study, 13 collagen-induced arthritic (CIA) rats and 12 healthy rats were given subcutaneous doses of either saline or 0.3 or 1.5 mg/kg per 2 days of MTX from day 21 to 43 post-induction. Blood samples were obtained at various times to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…DEX inhibits gene expression of TNF-α, IL-1β, and IL-6, and thus is more effective than the biologics which block only one of these cytokines. Our study results with etanercept, anakinra, and abatacept also agreed with the previous DEX study that TNF-α inhibitors are the most effective protein therapeutic for suppressing paw swelling in this animal model [12], and this is indicated by the greater inhibitory effect of etanercept ( I max = 0.289) [13] compared with that of anakinra ( I max = 0.279) [14], MTX ( I max = 0.160) [41], and abatacept ( I max = 0.161).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…DEX inhibits gene expression of TNF-α, IL-1β, and IL-6, and thus is more effective than the biologics which block only one of these cytokines. Our study results with etanercept, anakinra, and abatacept also agreed with the previous DEX study that TNF-α inhibitors are the most effective protein therapeutic for suppressing paw swelling in this animal model [12], and this is indicated by the greater inhibitory effect of etanercept ( I max = 0.289) [13] compared with that of anakinra ( I max = 0.279) [14], MTX ( I max = 0.160) [41], and abatacept ( I max = 0.161).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, such dosing groups were added to our subsequent studies with anakinra [14], methotrexate (MTX) [41], and abatacept. The doses selected in our studies were based on previous findings that showed successful use of the drug in similar animal models [39,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature survey revealed that there have been a few LC‐MS/MS methods reported for quantification of MTX alone (Turci et al ., ; Liu et al ., ) or with other drugs (Thappali et al ., ). The method described by Turci et al .…”
Section: Introductionmentioning
confidence: 99%
“…While the ODE models discussed above focused on the immunological mechanisms behind RA development and treatment, there is also a large class of ODE models that focus exclusively on the pharmacokinetics and pharmacodynamics of various drugs used to treat RA; see, for example, [75,80,48,49,113,60,58,77] and references therein. For example, [113] used a two-compartment pharmacokinetic ODE model to study the kinetics of the drug infliximab in RA patients, and how the kinetics are affected by inflammatory activity and methotrexate co-treatment.…”
Section: Stochastic/probabilistic Modelsmentioning
confidence: 99%